GOLFIG Chemo-Immunotherapy in Metastatic Colorectal Cancer Patients. A Critical Review on a Long-Lasting Follow-Up - Caraglia, Michele; Correale, Pierpaolo; Giannicola, Rocco; Staropoli, Nicoletta; Botta, Cirino; Pastina, Pierpaolo; Nesci, Antonello; Caporlingua, Nadia; Francini, Edoardo; Ridolfi, Laura; Mini, Enrico; Roviello, Giandomenico; et al. (Frontiers in Oncology, 2019)
Background: GOLFIG is a chemo-immunotherapy regimen established in preclinical models that combines gemcitabine + FOLFOX (fluoropyrimidine backbone coupled to oxaliplatin) poly-chemotherapy with low-dose s. c. recombinant interleukin-2 (rIL-2) and granulocyte-macrophage colony stimulating factor (GM-CSF). Promising antitumor effects in metastatic colorectal cancer (mCRC) patients were obtained in previous phase II and III trials. Here we report the results of 15 years of follow-up. Methods: This is a multi-institutional retrospective analysis including 179 mCRC patients receiving GOLFIG regimen between June 2002 and June 2018. Sixty-two of them received the treatment as frontline (enrolled in the GOLFIG-2 phase III trial) and 117 as second/third line (49 enrolled in the GOLFIG-1 phase II trial and 68 as compassionate use). One hundred twelve patients showed a primary left side and 67 a primary right side; K/N-ras mutational status was available in 74 cases, and an activating mutation was detected in 33. Kaplan–Meier and Cox regression analyses were carried out to relate PFS and OS with different parameters. Results: Overall, we recorded a mean PFS and OS of 15.28 (95% CI: 10.36–20.20) and 24.6 (95% CI: 19.07–30.14) months, respectively, with 14 patients surviving free of progression for 10 years. This regimen, in our updated survey of the GOLFIG-2 trial, confirmed superiority over FOLFOX in terms of PFS (hazard ratio (HR) = 0.58, p = 0.006) with a trend to a longer OS (HR = 0.69, P = 0.06) in the first line. Our analysis also confirmed significant antitumor activity in pre-treated patients, reporting a mean PFS and OS of 12.55 (95% CI: 7.19–17.9) and 20.28 (95% CI: 14.4–26.13) months, respectively. Immune-related adverse events (irAEs) were recorded in 24% of the cases and were related to a longer survival (HR = 0.36; P = 0.0001). Finally, patients' outcome was not correlated to sex, sidedness, and MT-K/N-ras. Conclusions: The GOLFIG regimen is a reliable underestimated therapeutic option in pre-treated mCRC patients and offers a strong rationale to design further trials.